Insights from using a Wearable Air Quality Sensor with Solar Energy Harvesting Features - Baguio Angelo Jay; Reyes Ronaldo; De Guzman Jaybie; Rosales Marc; Hizon John Richard (E3S Web of Conferences)
Air pollution is a growing global health concern, yet traditional monitoring infrastructure fails to assess individual exposure. This project presents a wearable air quality monitoring (AQM) system that provides real-time personal exposure insights. The system integrates the SEN-55 sensor (PM2.5, PM10, VOC) and SCD-41 sensor (CO2, temperature, humidity), transmitting data via Bluetooth Low Energy to a mobile application. The application offers air quality index (AQI) interpretation, detailed sensor data, and spatiotemporal tracking to evaluate personal exposure levels. To address the limitation of battery life in wearable devices, the system incorporates a battery-aware algorithm and solar energy harvesting, extending operational runtime. Sensor accuracy tests confirmed reliable performance for air quality measurements. Deployment campaigns revealed notable differences between indoor and outdoor air quality. Outdoor environments, particularly during commuting, showed elevated levels of particulate matter and VOCs, while indoor spaces with good ventilation and air conditioning had lower pollutant levels. However, CO2 concentrations were higher in poorly ventilated indoor areas. These results demonstrate the system’s effectiveness in capturing real-time environmental changes and providing actionable insights, enabling users to better manage their exposure to harmful pollutants.